2021
DOI: 10.1093/icb/icab030
|View full text |Cite
|
Sign up to set email alerts
|

Tail Length Evolution in Deer Mice: Linking Morphology, Behavior, and Function

Abstract: Determining how variation in morphology affects animal performance (and ultimately fitness) is key to understanding the complete process of evolutionary adaptation. Long tails have evolved many times in arboreal and semi-arboreal rodents; in deer mice, long tails have evolved repeatedly in populations occupying forested habit even within a single species (Peromyscus maniculatus). Here we use a combination of functional modeling, laboratory studies, and museum records to test hypotheses about the function of ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Furthermore, five inversions (inv7.2, inv14.0, inv15.0, inv18.0, inv21.0) were significantly associated with an ecotype-defining trait, tail length, in laboratory-raised F 2 hybrids 20 (P < 0.05, linear model) and, for all five, the forest arrangement was associated with longer tails (Fig. 6c), consistent with long tails being important for balance in arboreal habitats 36 . These five inversions together explain 23.0% of the variance in tail length (individually explaining 2.0-12.5% of the variance, with additive effects ranging from 1.1-2.7 mm change in tail length).…”
Section: Multiple Inversions Contribute To Local Adaptationmentioning
confidence: 57%
“…Furthermore, five inversions (inv7.2, inv14.0, inv15.0, inv18.0, inv21.0) were significantly associated with an ecotype-defining trait, tail length, in laboratory-raised F 2 hybrids 20 (P < 0.05, linear model) and, for all five, the forest arrangement was associated with longer tails (Fig. 6c), consistent with long tails being important for balance in arboreal habitats 36 . These five inversions together explain 23.0% of the variance in tail length (individually explaining 2.0-12.5% of the variance, with additive effects ranging from 1.1-2.7 mm change in tail length).…”
Section: Multiple Inversions Contribute To Local Adaptationmentioning
confidence: 57%
“…In 1909, Wilfred Osgood described several morphological differences—including tail length and coat color—that distinguish forest and prairie ecotypes of P. maniculatus ( 7 ). Long tails are thought to be beneficial for arboreality ( 8 , 9 , 23 ): Long tails have repeatedly evolved in association with forest habitat in deer mice ( 20 ) and across mammals ( 24 ), and forest mice are better climbers ( 23 ), with tail length differences between the ecotypes likely sufficient to affect climbing performance ( 25 ). Coat color is subject to pressure from visually hunting predators ( 19 ), and many mammals, including deer mice, evolve coats to match local soil color ( 9 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we genotyped the 13 polymorphic inversions in 136 samples across an environmental gradient and found that nine inversions show steep changes in frequency across the forest-prairie habitat transition (Figure 6B, Figure S7), suggesting that these inversions may be favored in alternate habitats. Furthermore, five inversions (inv7.2, inv14.0, inv15.0, inv18.0, inv21.0) are significantly associated with an ecotype-defining trait, tail length, in lab-raised F2 hybrids 19 , and for all five, the forest arrangement is associated with longer tails (Figure 6C), consistent with long tails being important for balance in arboreal habitats 34 . Inv15.0 was also previously found to be significantly associated with coat color, a second ecotype-defining trait 19 (Figure 6C).…”
Section: Resultsmentioning
confidence: 53%